FUNGAL CONTAMINATION IN FRESH RAISIN JUICE IN MOSUL CITY - Krmo, May Akram; Al_Rejaboo, Maha Akram Mohammad Ali (Journal of Medical Genetics and Clinical Biology, 2024)
Background: Fungal contamination in food and beverages, including fruit juices, poses significant health risks. Specific Background: This study investigates the extent of fungal contamination in fresh raisin juice collected from Mosul City and its suburbs, including Bashiqa, Al-Hamdaniya, Bartella, Al-Shekhan, Aqra, and Dohuk, over a period from January 2023 to April 2024. Knowledge Gap: Despite the potential for fungal contamination in fruit juices, detailed analyses of specific contamination rates and fungal species in this region have been lacking. Aims: The study aimed to identify and quantify fungal contamination in fresh raisin juice samples using Potato Dextrose Agar and Sabouraud Sucrose Agar, and to characterize the fungal isolates morphologically, biochemically, and molecularly. Results: Of the 40 samples tested, 100% were contaminated with fungi, yielding 121 isolates of various species. The highest contamination rates were observed for Candida spp. and Aspergillus spp., each constituting 27.3% of isolates. Other notable contaminants included Wickerhamomyces anomalus (12.39%), Saccharomyces cerevisiae (11.57%), and Rhodotorula spp. (8.26%). Additionally, lower rates of contamination were found for Penicillium spp., Exophiala dermatitidis, and several other species. Novelty: The study revealed a high prevalence of fungal contamination, including the identification of a novel Candida oleophila strain (GenBank accession PP961930.1). Implications: These findings highlight the significant fungal contamination in fresh raisin juice, which could have implications for food safety and quality control. The identification of specific fungal species and the novel strain underscores the need for stringent monitoring and improved processing practices to mitigate contamination risks.